TIR Справочник по конвенции мдп - Nations Unies (United Nations, 2019)
The first section describes the TIR transit system, its coverage, objective and functioning and analyses possible future developments. The second section contains the complete text of the TIR Convention. The third section contains related resolutions and recommendations.